Has banks' monitoring of other banks strengthened post-crisis? Evidence from the European overnight market - Eero Tölö; Esa Jokivuolle; Matti Viren (Bank of Finland, 2019)
Using the Eurosystem's proprietary interbank loan data from more than one thousand banks, practically all major banks in Europe for 2008-2016, we show that larger European banks have had a lower cost of overnight borrowing than smaller banks. The size premium remains significant after controlling for time, relationship lending, competitive environment of lenders, and bank risk characteristics but has decreased over time in countries that were stricken by the Sovereign Debt Crisis. Further, the ultra-short maturity of the overnight loans and the daily frequency at which we measure them provide for an ideal setting to use difference-in-differences analysis to study the potential effect of the Bank Recovery and Resolution Directive (BRRD) on the size premium in overnight rates and to avoid possible simultaneity problems. However, we find that changes in the size premium cannot be related to the implementation dates of the BRRD in different member countries.
URN:NBN:fi:bof-201909251502
Keywords: G21; G22; G24; G28; 330